Canlı renal transplant donörleri̇nde renal vasküler varyasyonların ve insi̇dental lezyonların sıklığı - BIYIKLI, ERHAN; ÇİMŞİT, CANAN; ÇİMŞİT, NURİ ÇAGATAY; KURŞUN, MELTEM (My University, 2021)
CANLI RENAL TRANSPLANT DONÖRLERİNDE RENAL VASKÜLER VARYASYONLARIN VE İNSİDENTAL LEZYONLARIN SIKLIĞIGİRİŞ -AMAÇ: Renal transplant verici adaylarının preoperatif değerlendirilmesinde abdominal BT anjiografi rutin olarak kullanılmaktadır. Preoperatif görüntüleme ile vasküler anatomi ve varyasyonlar optimal olarak değerlendirilebilmekte ve operasyonel komplikasyonların azaltılması amaçlanmaktadır. Abdominal BT anjiografi ile vasküler yapılara ilaveten non-vasküler insidental bulgular da gözlemlenmektedir. Çalışmamızda canlı böbrek vericilerinde renal damar varyasyonları ile insidental patolojilerin çeşit ve sıklığını tanımlamayı amaçlamaktayız.GEREÇ VE YÖNTEM 2012-2021 yılları arasında canlı böbrek vericisi olabilecek 22-72 yaş aralığında 76’sı erkek toplam 201 hasta çalışmaya dahil edildi. Hastaların abdominal BT anjiografi incelemeleri retrospektif olarak değerlendirildi. Renal arterler taraf, sayı ,çıkış yeri ve böbrekte sonlanma düzeyine; renal venler ise sayı,abdominal aort geçiş konumuna göre sınıflandırıldı. İnceleme sırasında karşılaşılan insidental bulgular gruplandırılarak sıklıkları değerlendirildi.BULGULAR: Çalışmamızdaki 201 hastanın 125’i kadın(%62) 76’sı erkekti(%38).Yaş aralığı 22-72 arasında değişmekteydi.(ort 46) Olguların 86’sında bilateral normal renal arter anatomisi mevcuttu. Renal arter varyasyonları %57 oranında iken ven varyasyonları %10 oranında görülmekteydi.(Resim a) Renal ven varyasyonu bulunan 12 olguda normal arter anatomisi saptandı. En sık renal arter varyasyonu sağ böbrek için aksesuar hiler renal arter(%11) iken sol böbrek için aortik alt polar arterdi(%8)(Resim b,c). 4 olguda birden fazla renal arter varyasyonu izlendi. Birden fazla renal arter görülme sıklığı sağ böbrekte %30 iken sol böbrekte %50 idi. Renal arter varyasyonu erkek olgularda daha sık görülmekteydi.(%58).Tüm olgularımızda renal arterler abdominal aortadan orijin almaktaydı. Renal arter ve ven varyasyonu birlikteliği 8 hastada mevcuttu. 148 olguda toplam 256 insidental bulgu tespit edildi. (Tablo).18 olguda Nutcracker sendromu düşündüren bulgular izlendi. En sık insidental bulgu olarak renal kortikal kistler saptandı ve kistlerin çoğu 3 cm den küçük bulundu. 8 olguda surrenal adenom mevcuttu. En sık rastlantısal karaciğer bulgusu hepatosteatoz idi.1 olguda insidental bulgu olarak patolojik olarak kanıtlı servikal kitle saptandı. TARTIŞMA -SONUÇ: Canlı renal transplant donörlerinde renal arter ve ven varyasyonlarının abdominal BT anjiografi ile saptanması transplantasyonun planlanması, operasyon esnasında karşılaşılabilecek risklerin önceden tespiti ve postoperatif komplikasyonları azaltmada oldukça yol göstericidir. Renal arter ve venin varyasyonları oldukça çeşitli olup %25-40 sıklıkta görülür. En sık görülen varyasyon, birden fazla sayıda renal arter olmasıdır. Canlı donörleri transplantasyona uygunluk açısından değerlendirme sürecinde abdominal BT anjiografi ile insidental bulgular da tespit edilebilmektedir . Çalışmamızda canlı böbrek vericilerinde renal damar varyasyonları ile insidental patolojilerin çeşit ve sıklığını tanımladık.Literatürle karşılaştırdığımızda renal arter varyasyonuna bizim çalışmamızda daha yüksek oranda rastlanılmıştır. ADDIN CSL_CITATION {"citationItems":[{"id":"ITEM-1","itemData":{"DOI":"10.1111/1754-9485.12618","ISSN":"17549485","PMID":"28466967","abstract":"Introduction: Variations of the renal arteries have been studied and published across various population groups, but similar information for the ethnically diverse nation of Australia is lacking. This study describes the pattern of renal artery anomalies in a section of the Australian population based on computed tomography (CT) angiograms of the abdomen and cadaveric dissection. Methods: The renal arterial vasculature of 594 kidneys from 300 subjects (28 cadavers, 272 CT) was studied. The number and pattern of renal arteries were categorised on the basis of laterality, point of origin and termination in the kidney (superior pole, hilum and inferior pole), symmetry and sex. Results: Multiple renal arteries were discovered in 22% of subjects and 12.12% of kidneys. The most common pattern observed was the presence of one variant renal artery (93.1%), compared to the finding of two (5.6%) and three (1.4%) multiple arteries. The aorta was the most frequent site of origin for anomalous vessels, while the hilum was the predominant point of entry. No significant difference was established between left- and right-sided kidneys (13.8% vs. 12.5%; P=0.627); however, unilateral distribution was more common than bilateral additional renal arteries (16.7% vs. 3.4%; P<0.01), and variations among males were more than females (27.2% vs. 15.2%; P<0.05). A higher rate of multiple renal arteries was noted in cadaveric dissections compared to CT images (46.4% vs. 19.5%; P<0.01). Conclusion: These findings provide application of an evidence-based teaching tool that facilitates education regarding renal arterial variations in Australia.","author":[{"dropping-particle":"","family":"Tardo","given":"Daniel T.","non-dropping-particle":"","parse-names":false,"suffix":""},{"dropping-particle":"","family":"Briggs","given":"Christopher","non-dropping-particle":"","parse-names":false,"suffix":""},{"dropping-particle":"","family":"Ahern","given":"Gerard","non-dropping-particle":"","parse-names":false,"suffix":""},{"dropping-particle":"","family":"Pitman","given":"Alexander","non-dropping-particle":"","parse-names":false,"suffix":""},{"dropping-particle":"","family":"Sinha","given":"Sankar","non-dropping-particle":"","parse-names":false,"suffix":""}],"container-title":"Journal of Medical Imaging and Radiation Oncology","id":"ITEM-1","issue":"5","issued":{"date-parts":[["2017"]]},"page":"643-649","title":"Anatomical variations of the renal arterial vasculature: An Australian perspective","type":"article-journal","volume":"61"},"uris":["http://www.mendeley.com/documents/?uuid=788348f6-67a3-41d7-b503-efc216ffebc3"]}],"mendeley":{"formattedCitation":"(1)","plainTextFormattedCitation":"(1)","previouslyFormattedCitation":"(1)"},"properties":{"noteIndex":0},"schema":"https://github.com/citation-style-language/schema/raw/master/csl-citation.json"}(1) Polar renal arteri hiler artere göre daha sık tespit etmiş olmamız literatür bulguları ile örtüşmektedir.ADDIN CSL_CITATION {"citationItems":[{"id":"ITEM-1","itemData":{"DOI":"10.1002/ca.10236","ISSN":"08973806","PMID":"15108340","abstract":"A thorough knowledge of the variations of the renal artery has grown in importance with the increasing numbers of renal transplants, vascular reconstructions, and various surgical and radiologic techniques. The literature indicates that multiple renal arteries are found in 9-76% of cadavers. The purpose of this study is to establish the incidence and characteristics of variations of renal arteries in Thais. A total of 267 Thai cadavers were dissected in the anatomy laboratory. The anatomical findings included: a single hilar artery in 82% of cases; double renal arteries in 17% of cases (one hilar artery with an upper polar artery occurred in 7%; two hilar arteries in 7%, and one hilar artery combined with one lower polar artery in 3%); and triple renal arteries occurred in 1% (two hilar arteries with one upper polar artery in 0.4% and two hilar arteries with one lower polar artery in 0.6%). In preparation for interventions, such as living renal donation, vascular reconstruction, renovascular hypertension, or radical nephrectomy, the results indicate that preoperative renal imaging is necessary and that operative techniques with attention to multiple renal arteries should be considered. © 2004 Wiley-Liss, Inc.","author":[{"dropping-particle":"","family":"Khamanarong","given":"Kimaporn","non-dropping-particle":"","parse-names":false,"suffix":""},{"dropping-particle":"","family":"Prachaney","given":"P.","non-dropping-particle":"","parse-names":false,"suffix":""},{"dropping-particle":"","family":"Utraravichien","given":"A.","non-dropping-particle":"","parse-names":false,"suffix":""},{"dropping-particle":"","family":"Tong-Un","given":"T.","non-dropping-particle":"","parse-names":false,"suffix":""},{"dropping-particle":"","family":"Sripaoraya","given":"K.","non-dropping-particle":"","parse-names":false,"suffix":""}],"container-title":"Clinical Anatomy","id":"ITEM-1","issue":"4","issued":{"date-parts":[["2004"]]},"page":"334-336","title":"Anatomy of Renal Arterial Supply","type":"article-journal","volume":"17"},"uris":["http://www.mendeley.com/documents/?uuid=2231b629-d562-4df7-bac2-4d1c9f5e2318"]}],"mendeley":{"formattedCitation":"(2)","plainTextFormattedCitation":"(2)","previouslyFormattedCitation":"(2)"},"properties":{"noteIndex":0},"schema":"https://github.com/citation-style-language/schema/raw/master/csl-citation.json"}(2) Venöz varyasyon olarak en sık sirkumaortik sol renal ven saptamamıza rağmen diğer çalışmalarda bunu destekleyici bir veriye ulaşamadık.ADDIN CSL_CITATION {"citationItems":[{"id":"ITEM-1","itemData":{"DOI":"10.4103/njcp.njcp_237_17","ISSN":"11193077","PMID":"29984713","abstract":"Background: A broad spectrum of renal vascular variations has been reported by anatomists and radiologists. The prevalence of these variations is extremely divergent in different populations. Therefore, radiologists and surgeons in different climes must be knowledgeable about the type and prevalence of the variants in their area of practice to avoid diagnostic pitfalls and for optimization of surgical techniques. Objective: The objective of this study is to describe the types and prevalence of renal vascular variations among patients undergoing contrast-enhanced computerized tomography (CECT) of the abdomen in a Nigerian population, as well as provide a concise review of literature on the embryological basis and clinical significance of the identified variations. Materials and Methods: This study was a retrospective review of 200 CECT of the abdomen to identify variations of arterial (accessory, early branching, and precaval) and venous (multiple, retroaortic, and circumaortic) anatomy of the kidneys. Results: We studied 200 patients, 102 (51%) females and 98 (49%) males. Age range is 18-90 years (mean = 53.08 ± 17.01). Prevalence of any renal vascular variations was 50%, arterial variations were 37%, and venous variations were 13%. Variations were significantly more common in males, P = 0.000075. The most common arterial variant was the accessory renal artery (23%) seen in 10% (right) and 13.0% (left); early branching was seen in 4.0% (right) and 0.5% (left) as well as precaval right renal artery seen in 4.5%. Venous variants were late confluence 3.0% (right) and 2.5% (left); multiple veins was seen in 2.5% (right) and 2.5% (left) as well as retroaortic left renal vein seen in 2.0%. The inferior polar accessory artery was the most prevalent accessory artery. Early arterial bifurcation was significantly more common on the right (P = 0.016) while other vascular variants showed no statistically significant association with laterality. Conclusion: Variation of renal vascular anatomy is a frequent finding among Nigerians. Radiologists and surgeons must be aware of these variants for optimization of surgical techniques.","author":[{"dropping-particle":"","family":"Famurewa","given":"O. C.","non-dropping-particle":"","parse-names":false,"suffix":""},{"dropping-particle":"","family":"Asaleye","given":"C. M.","non-dropping-particle":"","parse-names":false,"suffix":""},{"dropping-particle":"","family":"Ibitoye","given":"B. O.","non-dropping-particle":"","parse-names":false,"suffix":""},{"dropping-particle":"","family":"Ayoola","given":"O. O.","non-dropping-particle":"","parse-names":false,"suffix":""},{"dropping-particle":"","family":"Aderibigbe","given":"A. S.","non-dropping-particle":"","parse-names":false,"suffix":""},{"dropping-particle":"","family":"Badmus","given":"T. A.","non-dropping-particle":"","parse-names":false,"suffix":""}],"container-title":"Nigerian Journal of Clinical Practice","id":"ITEM-1","issue":"7","issued":{"date-parts":[["2018"]]},"page":"840-846","title":"Variations of renal vascular anatomy in a nigerian population: A computerized tomography studys","type":"article-journal","volume":"21"},"uris":["http://www.mendeley.com/documents/?uuid=e18aef01-3096-4944-be87-fd974d26dcec"]}],"mendeley":{"formattedCitation":"(3)","plainTextFormattedCitation":"(3)","previouslyFormattedCitation":"(3)"},"properties":{"noteIndex":0},"schema":"https://github.com/citation-style-language/schema/raw/master/csl-citation.json"}(3) Olası canlı renal transplant donörlerinde insidental bulgulara baktığımızda en sık bulgu bizim çalışmamızda olduğu gibi renal kortikal kist olarak tanımlanmıştır.ADDIN CSL_CITATION {"citationItems":[{"id":"ITEM-1","itemData":{"DOI":"10.6002/ect.2017.0340","ISSN":"13040855","PMID":"30119619","abstract":"Objectives: Prospective renal donors are a select population of healthy individuals who have been thoroughly screened for significant comorbidities before they undergo multidetector computed tomo - graphy. Our aim was to determine the prevalence of incidental findings on preoperative multidetector computed tomography in a healthy cohort of potential living donors for kidney transplant. Materials and Methods: A prospective study was performed of prospective living kidney transplant donors at a national kidney transplant center. Study inclusion criteria were all potential kidney donors who underwent multidetector computed tomography during the living-donor assessment process over a 5-year period (January 2012 to 2017). Results: Our cohort included 375 potential living donors who had multidetector computed tomo - graphy; mean age was 44.33 years (range, 21-71.5 y). In total, there were 228 incidental findings identified in 158 individuals. Of the 375 potential donors, 193 (51%) proceeded to living donor nephrectomy. On multidetector computed tomography, 97 incidental findings were identified in the donor cohort versus 131 in the cohort that did not proceed to donation. Bosniak 1 renal cysts were the most common incidental finding (n = 46) followed by liver cysts < 1.5 cm (n = 42) and urinary tract calculi (n = 21). There was 1 incidentally detected pathologically proven malignancy. Conclusions: A variety of incidentally detected lesions of moderate to high importance were detected in this healthy donor cohort. Individuals undergoing assessment with multidetector computed tomography for living donor nephrectomy should be counseled on medical, financial, and psychological implications of incidentally detected lesions during the kidney transplant evaluation process.","author":[{"dropping-particle":"","family":"O’Neill","given":"Damien C.","non-dropping-particle":"","parse-names":false,"suffix":""},{"dropping-particle":"","family":"Davis","given":"Niall F.","non-dropping-particle":"","parse-names":false,"suffix":""},{"dropping-particle":"","family":"Murray","given":"Timothy","non-dropping-particle":"","parse-names":false,"suffix":""},{"dropping-particle":"","family":"Lee","given":"Michael J.","non-dropping-particle":"","parse-names":false,"suffix":""},{"dropping-particle":"","family":"Little","given":"Dilly","non-dropping-particle":"","parse-names":false,"suffix":""},{"dropping-particle":"","family":"Morrin","given":"Martina M.","non-dropping-particle":"","parse-names":false,"suffix":""}],"container-title":"Experimental and Clinical Transplantation","id":"ITEM-1","issue":"2","issued":{"date-parts":[["2019"]]},"page":"177-182","title":"Prevalence of incidental findings on multidetector computed tomography in potential nephrectomy donors: A prospective observational study","type":"article-journal","volume":"17"},"uris":["http://www.mendeley.com/documents/?uuid=ed9db7ca-1d9c-4f48-91a4-be23fca18ae2"]}],"mendeley":{"formattedCitation":"(4)","plainTextFormattedCitation":"(4)","previouslyFormattedCitation":"(4)"},"properties":{"noteIndex":0},"schema":"https://github.com/citation-style-language/schema/raw/master/csl-citation.json"}(4) Sonuç olarak, Çalışmamızda görüntüleme sırasında saptanan insidental bulgular transplantasyona büyük oranda engel oluşturmamıştır ve Renal transplantasyon öncesi renal arter- ven varyasyonlarını tespit ederek olası intra-postoperatif komplikasyonları azaltmak için BT anjiografi noninvazif,hızlı,etkin bir görüntüleme yöntemi olarak tercih edilmelidir.Anahtar kelimeler: Renal transplantasyon,varyasyon,BT anjiografiKaynaklarADDIN Mendeley Bibliography CSL_BIBLIOGRAPHY 1. Tardo DT, Briggs C, Ahern G, Pitman A, Sinha S. Anatomical variations of the renal arterial vasculature: An Australian perspective. J Med Imaging Radiat Oncol. 2017;61(5):643–9. 2. Khamanarong K, Prachaney P, Utraravichien A, Tong-Un T, Sripaoraya K. Anatomy of Renal Arterial Supply. Clin Anat. 2004;17(4):334–6. 3. Famurewa OC, Asaleye CM, Ibitoye BO, Ayoola OO, Aderibigbe AS, Badmus TA. Variations of renal vascular anatomy in a nigerian population: A computerized tomography studys. Niger J Clin Pract. 2018;21(7):840–6. 4. O’Neill DC, Davis NF, Murray T, Lee MJ, Little D, Morrin MM. Prevalence of incidental findings on multidetector computed tomography in potential nephrectomy donors: A prospective observational study. Exp Clin Transplant. 2019;17(2):177–82.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE